MENGUKUR KEPUASAN PELANGGAN MEBEL KEN KEN DENGAN METODE SERVICE QUALITY (SERVQUAL) - Teresia C.; yun - suprani; Muhammad Said; Akbar Malik Muharam (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2026)
Customer satisfaction is one of the important things in companies engaged in the furniture retail sector, because it is an indicator of business success. Therefore, this study aims to determine how satisfied customers are at the Kenken furniture store and also to find out what attributes need to be improved to increase customer satisfaction at the Kenken furniture store. The method used in this study is the Service Quality method which is used to determine the level of customer satisfaction. From the results of this study, it is clear that Kenken furniture store customers are not satisfied with the services provided. The analysis was carried out using the Servqual Method (Service Quality) on the service dimension. The service dimensions include Tangibles, Reliability, Responsiveness, Assurance, and Empathy. And from the results of the study, it can also be seen that the Responsiveness variable has the results that best meet customer expectations, namely with a gap value of 4.00. Meanwhile, the variable that least meets customer expectations is the Reliability variable which has a gap of -13.67.